Effect of Compact Density of MoO2 Powders on Densification Kinetics and Grain Growth During Sintering Processes - Jongbeom Lee; Jaehoon Jung; Hyowon Lee; Jaesoung Park; Haguk Jeong (Crystals)
MoO2 powders compacted under different uniaxial pressures ranging from 100 to 800 MPa, corresponding to the compact densities ranging from 55% to 65%, respectively, were sintered at targeted temperatures within 650–1050 °C for 1 h in an N2 atmosphere. Then, their densification kinetics and grain growth were investigated. With regard to the densification of MoO2 powders at room temperature, a linear relationship was observed between the compact density and log pressure in the uniaxial pressure range without fracture and local deformation. The relative densities of the sintered MoO2 samples increased with increasing compact density and sintering temperature. At a given sintering temperature, the sample with the highest compact density exhibited the best densification rate. The grain size in the sintered samples was proportional to the relative density, and the grain growth obeyed the Arrhenius equation. The sintered samples with 55%, 60%, and 65% densities during the sintering process have different activation energies values depending on the sintering temperature. At low sintering temperatures, the activation energies for 55%, 60%, and 65% compact densities were 50.8, 39.6, and 26.1 kJ/mol, respectively, and at higher sintering temperatures, the corresponding values were 19.8, 21.5, and 25.4 kJ/mol.